2015
DOI: 10.1186/s12990-015-0061-y
|View full text |Cite
|
Sign up to set email alerts
|

Anoctamin-1 Cl Channels in Nociception: Activation by an N-Aroylaminothiazole and Capsaicin and Inhibition by T16A[inh]-A01

Abstract: BackgroundAnoctamin 1 (ANO1 or TMEM16A) Ca2+-gated Cl− channels of nociceptor neurons are emerging as important molecular components of peripheral pain transduction. At physiological intracellular Cl− concentrations ([Cl−]i) sensory neuronal Cl− channels are excitatory. The ability of sensory neuronal ANO1 to trigger action potentials and subsequent nocifensive (pain) responses were examined by direct activation with an N-aroylaminothiazole. ANO1 channels are also activated by intracellular Ca2+ ([Ca2+]i) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 63 publications
2
25
0
1
Order By: Relevance
“…This confirmed previous reports demonstrating that TRPV1 and ANO1 channels can directly interact with each other [5]. Furthermore, blockers of ANO1 channels were shown to reduce the excitatory actions of the TRPV1 channel activator capsaicin on sensory neurons, on the one hand, and the nocifensive behavior of mice in response to TRPV1 activation, on the other hand [5, 6]. The presumed underlying process is the gating of CaCCs by Ca 2+ which enters the neurons via TRPV1 channels (Figure 1).…”
supporting
confidence: 90%
“…This confirmed previous reports demonstrating that TRPV1 and ANO1 channels can directly interact with each other [5]. Furthermore, blockers of ANO1 channels were shown to reduce the excitatory actions of the TRPV1 channel activator capsaicin on sensory neurons, on the one hand, and the nocifensive behavior of mice in response to TRPV1 activation, on the other hand [5, 6]. The presumed underlying process is the gating of CaCCs by Ca 2+ which enters the neurons via TRPV1 channels (Figure 1).…”
supporting
confidence: 90%
“…RNAi knockdown or genetic deletion of TMEM16A from DRG neurons also substantially attenuated thermal hyperalgesia in both inflammatory and neuropathic pain models (Lee et al, ; Liu et al, ). Moreover, a recent study also showed that Eact activated DRG neurons and induced pain response, both of which were suppressed by the TMEM16A inhibitor A01 (Deba and Bessac, ). Indeed, we also found that co‐expression of TMEM16A potentiated capsaicin‐activated currents in mTRPV1‐expressing HEK293T cells, suggesting that Eact activation of TMEM16A might also contribute to Eact‐elicited sensory hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Although different experimental settings, cell culture conditions, and differences between HEK293T cells and DRG neurons might partly account for the discrepancy of Eact responses in DRG and heterologous cells between these two studies (Deba and Bessac, ), our results using TRPV1 knockout mice clearly demonstrated that Eact‐induced excitation and sensory hypersensitivity require functional TRPV1 channels, suggesting that Eact is not an ideal tool to dissect the function of TMEM16A in the primary sensory neurons because it could directly activate TRPV1 in the same cells. Because TRPV1 is a dominant initiator of pain and itch in the primary sensory neurons, Eact activation of TRPV1 could override TMEM16A‐mediated Eact responses.…”
Section: Discussionmentioning
confidence: 99%
“…TRPV1 mediated Ca 2+ influx activates anoctamine 1 (ANO1), Ca 2+ -activated Cl − channels in nociceptive terminals, which leads to further depolarization [78]. Indeed, pharmacological inhibition of ANO1 attenuates capsaicin-mediated acute nocifensive behaviors in rodents [78,79]. …”
Section: Functional and Histological Effectsmentioning
confidence: 99%